Nitrogen use efficiency in potato crop (Solanum tuberosum L.) - Amel Marouani; Youcef Harbeoui (Acta Agronómica)
In Tunisia, nitrogen fertilization of potato combines the use of mineral fertilizers with high doses of N without reaching expected yield. . In order to improve the system productivity of tunisian exploitation, an experiment was conducted at the Technical Center of Potato and Artichoke (CTPTA) Saida - Manouba. Three N treatments (0, 50 and 200 kg ha-1) and three varieties of potato (Spunta, Bellini and Atlas) were used. The aim of this study was to evaluate the efficiency of N use in Tunisian agricultural condition of potato crop as of determining the effect of different doses of N on the parameters of growth and development of potato crop, and fixing the optimal dose of N which allows the improvement of potato crop yield. Results indicated that higher yields and N extracted by tubers were determined with the highest N availability. The calculation of the coefficient of apparent use of N indicated low N use efficiency due to limited N availability. Based on the balance method, the concentration of nitrates in depth was high. The software Mabia-Région showed nitrate the loss of by drainage.